Review of Intelligent Routing Technology in Integrated Satellite-Ground Network - Suzhi CAO; Xue SUN; Houpeng WANG; Jiarong HAN; Siyan PAN; Lei YAN (天地一体化信息网络)
In view of the complex routing problems faced by the integrated satellite-ground network, the research progress of softwaredefi ned integrated satellite-ground network and intelligent routing was investigated.The training and deployment schemes of on-orbit routing mechanisms based on deep reinforcement learning were discussed, and a specifi c analysis was made in conjunction with the space intelligent computing platform.